2020
DOI: 10.1016/j.ijmedinf.2019.104013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of context-specific alerts for potassium-increasing drug-drug interactions: A pre-post study

Abstract: Objective: To investigate whether context-specific alerts for potassium-increasing drug-drug interactions (DDIs) in a clinical decision support system reduced the alert burden, increased alert acceptance, and had an effect on the occurrence of hyperkalemia. Materials and Methods:In the pre-intervention period all alerts for potassium-increasing DDIs were level 1 alerts advising absolute contraindication, while in the post-intervention period the same drug combinations could trigger a level 1 (absolute contrain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…In the approach, the development of context-specific alarms for potassium-increasing DDIs and patient-specific risk assessments for hyperkalemia will help reduce the number of unnecessary alerts. This finding broadly supports the work in this area by KM Muylle et al (2020) who found that the optimized CDS, which uses context factors for the individual risk assessment of hyperkalemia, significantly reduced the alert burden by 92.8% [35].…”
Section: Discussionsupporting
confidence: 87%
“…In the approach, the development of context-specific alarms for potassium-increasing DDIs and patient-specific risk assessments for hyperkalemia will help reduce the number of unnecessary alerts. This finding broadly supports the work in this area by KM Muylle et al (2020) who found that the optimized CDS, which uses context factors for the individual risk assessment of hyperkalemia, significantly reduced the alert burden by 92.8% [35].…”
Section: Discussionsupporting
confidence: 87%
“…To go further, this taxonomic model hierarchically classifying modulators of alert acceptance has to be understood as a starting point to receive more summarized evidence and to understand context and relationships of individual modulators influencing alert acceptance. The complex intervention reported by Muylle and coworkers consists for example of parameters that can be allocated to various factors (i.e., inclusion of patient-specific context factors, tiering of alert according to severity, and filtering, clustering or deactivation of alerts) in this model 60,64 and as they evaluated several factors at one time and although the intervention had a significant impact overall, the impact of each single factor was only partly sufficient for significance.…”
Section: Further Implications On Alert Acceptancementioning
confidence: 99%
“…This means that bias and a potential risk of inconsistency cannot be discounted, despite two reviewers having assigned the modulators independently and discussed differences until congruency was reached. It is at least as important to mention that extracted parameters from complex interventions composed of different parameters were allocated to various 64 or the most appropriate factors 60 according to the description in the original article. Each quantitative parameter is explained in ►Table 1 so that complex interventions are also presented as transparent as the original article allows.…”
Section: Limitationsmentioning
confidence: 99%
“…Several approaches to decreasing over-alerting and alert fatigue have been developed and tested. These include (1) changing the way alerts are displayed [19][20][21][22][23][24][25], (2) refining the alerts' relevance by filtering them according to clinical veracity [10,11,17,20,21,[26][27][28][29] or postalert quality assessment by a group of practitioners [29], and (3) managing chronological aspects [19][20][21]23,24,30]. It has also been suggested that the relevance of alerts can be increased by taking into account the level of evidence for the DDI [20,21] and the seriousness of the outcome [10,17,20,21,27,29,31].…”
Section: Introductionmentioning
confidence: 99%